Visual outcome in patients undergoing minimally invasive vitrectomy surgery in rhegmatogenous retinal detachment - V., Soumya; John, Biju; Mamman, Accamma (International Journal of Advances in Medicine, 2021)
Background: Micro-incision vitrectomy surgery otherwise called minimally invasive vitrectomy surgery (MIVS) is undoubtedly one of the most impressive evolutions in the surgical retina field of the past decade. This self-healing suture less procedure is safe and reliable with rapid visual recovery. The present study enlightens the visual outcome following MIVS for rhegmatogenous retinal detachment. Methods: This prospective study was done in 68 patients who underwent MIVS for rhegmatogenous retinal detachment. A detailed ocular examination of the patients undergoing MIVS was done. Outcome of the surgery was assessed in terms of functional and anatomical success after one week, 6 weeks and third month. Results: Of the 68 patients, maximum number of patients was in the age group of 51-60 years. Risk factors were previous cataract surgery in 28%, lattice degeneration in 26%, trauma in 22%, myopia in 18% and no specific risk factors in 6%. Mean preoperative BCVA was log MAR 2.16±0.37 and mean post-operative BCVA was log MAR 1.22±0.35 with p value of <0.001 on paired t test indicating the difference was statistically significant. Functional success was achieved in 58% and anatomical success in 94% patients. Conclusions: Visual outcome following MIVS was good for rhegmatogenous retinal detachment. Secondary glaucoma and development or progression of cataract was found to be the major complication following MIVS. MIVS is a suture less safe surgery facilitating early visual recovery and associated with minimal complications.